Hyperhomocystinemia in patients with coronary artery disease - Faria-Neto,J.R. (2006)
Hyperhomocystinemia has been related to an increased risk of cardiovascular disease in several studies. The C677T polymorphism for the gene that encodes the methylenetetrahydrofolate reductase enzyme (MTHFR) and low plasma folate levels are common causes of hyperhomocystinemia. Due to differences in nutritional patterns and genetic background among different countries, we evaluated the role of hyperhomocystinemia as a coronary artery disease (CAD) risk factor in a Brazilian population. The relation between homocysteine (Hcy) and the extent of CAD, measured by an angiographic score, was determined. A total of 236 patients referred for coronary angiography for clinical reasons were included. CAD was found in 148 (62.7%) patients and 88 subjects had normal or near normal arteries. Patients with CAD had higher Hcy levels [mean (SD)] than those without disease (14 (6.8) vs 12.5 (4.0) µM; P = 0.04). Hyperhomocystinemia (Hcy >17.8 µM) prevalence was higher in the CAD group: 31.1 vs 12.2% (P = 0.01). After adjustment for major risk factors, we found an independent association between hyperhomocystinemia and CAD (OR = 2.48; 95% CI = 1.02-6.14). Patients with a more advanced coronary score had a higher frequency of hyperhomocystinemia and tended to have higher mean Hcy levels. An inverse relation between plasma folate and Hcy levels was found (r = -0.14; P = 0.04). Individuals with the MTHFR C677T polymorphism had a higher prevalence of hyperhomocystinemia than those without the mutated allele. We conclude that hyperhomocystinemia is independently associated with CAD, with a positive association between Hcy level and disease severity.